2022
DOI: 10.1126/sciimmunol.abn8144
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the thymus master regulator Foxn1

Abstract: FOXN1 is a transcription factor critical for the development of both thymic epithelial cell (TEC) and hair follicle cell (HFC) compartments. However, mechanisms controlling its expression remain poorly understood. To address this question, we performed thorough analyses of the evolutionary conservation and chromatin status of the Foxn1 locus in different tissues and states and identified several putative cis-regulatory regions unique to TECs versus HFCs. Furthermore, experiments using g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 91 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, our investigation revealed significant epigenetic changes in both mouse and human TECs during aging, which can impact various aspects of TEC function and senescence. Previous studies have demonstrated the influence of epigenetic changes on the expression of Foxn1, the epithelial-to-mesenchymal transition of TECs to adipocytes, and the expression of tissue-restricted self-Ags ( 39 40 ). Moreover, our analysis also highlighted potential involvement of other unstudied epigenetic factors, such as histone methylation, histone acetylation, and DNA methylation, which may contribute to age-related TEC dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our investigation revealed significant epigenetic changes in both mouse and human TECs during aging, which can impact various aspects of TEC function and senescence. Previous studies have demonstrated the influence of epigenetic changes on the expression of Foxn1, the epithelial-to-mesenchymal transition of TECs to adipocytes, and the expression of tissue-restricted self-Ags ( 39 40 ). Moreover, our analysis also highlighted potential involvement of other unstudied epigenetic factors, such as histone methylation, histone acetylation, and DNA methylation, which may contribute to age-related TEC dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In the mammalian thymus, Foxn1 controls a complex genetic network [6–10], which ensures the generation of mature T cells expressing a diverse and self‐tolerant repertoire of T cell receptors. Foxn1 controls the expression of chemokine genes, such as Cxcl12 , which leads to the attraction of hematopoietic progenitors to the thymus anlage.…”
Section: Introductionmentioning
confidence: 99%